Decreased Modulation of EEG Oscillations in High-Functioning Autism during a Motor Control Task - Ewen, Joshua B.; Lakshmanan, Balaji M.; Pillai, Ajay S.; McAuliffe, Danielle; Nettles, Carrie; Hallett, Mark; Crone, Nathan E.; Mostofsky, Stewart H. (Frontiers in Human Neuroscience, 2016)
Autism spectrum disorders (ASD) are thought to result in part from altered cortical excitatory-inhibitory balance; this pathophysiology may impact the generation of oscillations on EEG. We investigated premotor-parietal cortical physiology associated with praxis, which has strong theoretical and empirical associations with ASD symptomatology. 25 children with high-functioning ASD (HFA) and 33 controls performed a praxis task involving the pantomiming of tool use, while EEG was recorded. We assessed task-related modulation of signal power in alpha and beta frequency bands. Compared with controls, subjects with HFA showed 27% less left central (motor/premotor) beta (18-22 Hz) event-related desynchronization (ERD) (p = 0.030), as well as 24% less left parietal alpha (7-13 Hz) ERD (p = 0.046). Within the HFA group, blunting of central ERD attenuation was associated with impairments in clinical measures of praxis imitation (r = -0.4; p = 0.04) and increased autism severity (r = 0.48; p = 0.016). The modulation of central beta activity is associated, among other things, with motor imagery, which may be necessary for imitation. Impaired imitation has been associated with core features of ASD. Altered modulation of oscillatory activity may be mechanistically involved in those aspects of motor network function that relate to the core symptoms of ASD.